An audit of performance nutrition services in English soccer academies: implications for optimising player development. Issue 2 (3rd April 2023) - Carney, Daniel J.; Hannon, Marcus P.; Coleman, Nicholas M.; Murphy, Rebecca C.; Close, Graeme L.; Morton, James P.
ABSTRACT: To audit the current provision of performance nutrition services provided to male adolescent players within academies from the English soccer leagues. Practitioners from all 89 academies (status categorised as one-four according to the Elite Player Performance Plan, EPPP) completed an online survey to audit: a) job role/professional accreditation status of persons delivering nutrition support, b) activities inherent to service provision, c) topics of education, d) on-site food, fluid and supplement provision and e) nutritional related data collected for objective monitoring. More full-time accredited nutritionists are employed within category one (14/26) versus category two (0/18), three (1/41) and four (0/4). Respondents from category one clubs report more hours of monthly service delivery (62 ± 57 h) than category two (12 ± 9 h), three (14 ± 26 h) and four (12 ± 14 h), inclusive of one-to-one player support and stakeholder education programmes. Category one practitioners reported a greater prevalence of on-site food, fluid and supplement provision on training and match days. Across all categories, players from the professional development phase receive more frequent support than players from the youth development phase, despite the latter corresponding to the most rapid phase of growth and maturation. We report distinct differences in the extent of service provision provided between categories. Additionally, players from all categories receive nutrition support from non-specialist staff. Data demonstrate that performance nutrition appears an under-resourced component of academy sport science and medicine programmes in England, despite being an integral component of player development.